Managing the economy, managing the people narratives of economic life in Britain from Beveridge to Brexit - Tomlinson, Jim 1951- (Oxford University Press, 2017)
This is a distinctive new account of British economic life since the Second World War, showing how successive governments have managed the British people by managing the narrative on economic matters, from the post-war notion of austerity to the recent 'debts and deficits' of post-financial crash Britain
This edition previously issued in print: 2017. - Includes bibliographical references and index
Keywords: Geschichte 1900-; Wirtschaftstheorie; Wirtschaft; Great Britain / Economic conditions / 1945-1964; Great Britain / Economic conditions / 1964-1979; Great Britain / Economic conditions / 1979-1997; Great Britain / Economic conditions / 1997-; Großbritannien